Photo detector-based indoor positioning systems variants: A new look. (May 2020) - Khan, Muhammad Nasir; Jamil, M.; Gilani, S.O.; Ahmad, I.; Uzair, M.; Omer, H.
Abstract: Indoor positioning system (IPS) coupling with photo-detectors at the receiving end has gained much attention from the consumers. The accuracy level using the global positioning system (GPS) is not up-to-the-mark in the indoor environment. Meanwhile, visible light communication (VLC) employing the optical transmitter, e.g., light-emitting diodes (LEDs), is considered a promising candidate nowadays because of its enormous advantages. To better understand the VLC channel model, a comprehensive review is presented. An investigation of the LED-based IPS, employed for the position calculation using various techniques, is intensely discussed. The types of different photodetectors-based IPSs are elaborated along with the metrics. A comparison of various IPSs is developed to select the optimum one better. A new look of the IPS is proposed with extended features and better accuracy. A conclusion is drawn in this field for researchers to enhance VLC-based systems towards future research.